Investment Banking and Security Market Development : Does Finance Follow Industry? - Anand, Bharat (IMF Working Papers; Working Paper, 2001)
Long-term relationships between business firms and investment banks are pervasive in developed security markets and there is evidence that better monitoring and information result from these relationships. Therefore, security markets should allocate resources better when an investment banking industry exists. We study the necessary conditions for the emergence of sustainable relationships and explore whether policy can foster them. We show that policy can help alleviate the costs of relationships, but an investment banking industry will not emerge with only a small number of large firms.